Handbook of LGBTQ-Affirmative Couple and Family Therapy - Harvey, Rebecca; Murphy, Megan J.; Bigner, Jerry J.; Wetchler, Joseph L. (Routledge, 2021)
This comprehensive second edition inspires therapists to utilize clinical work to pragmatically address intersectional oppressions, lessen the burden of minority stress, and implement effective LGBTQ affirmative therapy. A unique and important contribution to LGBTQ literature, this handbook includes both new and updated chapters reflecting cutting-edge intersectional themes like race, ethnicity, polyamory, and monosexual normativity. A host of expert contributors outline the best practices in affirmative therapy, inspiring therapists to guide LGBTQ clients into deconstructing the heteronormative power imbalances that undermine LGBTQ relationships and families. There is also an increased focus on clinical application, with fresh vignettes included throughout to highlight effective treatment strategies. Couple and family therapists and clinicians working with LGBTQ clients, and those interested in implementing affirmative therapy in their practice, will find this updated handbook essential.
Keywords: dept.mft

Supervised Visitation. - Lynch, Barbara (2000)
Keywords: dept.mft; faculty_collection; sabbatical_report

Normal Madness, Murder and Mayhem - Lynch, J. Edward (Xlibris Corp, 2008)
Keywords: dept.mft; faculty_collection

Nurturing Queer Youth: Family Therapy Transformed - Stone Fish, Linda; Harvey, Rebecca G. (Norton, 2005)
Keywords: Case studies; Case studies; Gay youth; Counseling of; Bisexual youth; Counseling of; Family psychotherapy; Family relationships; Gay youth; dept.mft; faculty_collection

North Star Facilitator's Manual - Manke, Nancy; Matheny, Karla; De Barbieri, Patricia (s.n., 2004)
A program for school-age girls designed to promote social and emotional learning, to enhance resiliency, improve self confidence and aid in the prevention of future problems such as eating disorders, drug abuse and poor academic performance. - p. [1]
Keywords: Self-esteem in women; Study and teaching; Study and teaching; Self-esteem in children; dept.mft; faculty_collection

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found

Undergraduates and intercultural communication competence: Creating a plan for performance - Madlock, A. (International Journal of Learning, 2009)
Some studies indicate that students develop intercultural communication competence through interaction in multicultural classrooms. However, what happens when classrooms are predominately homogenous and student exposure to other cultures is limited to media representations? It is not uncommon to find this situation still existing on some college campuses in the United States of America, where students have never come in contact with individuals different from themselves, beyond service industry workers, if any contact is made at all. The idea of establishing a significant relationship with someone culturally different is not given any thought. As an instructor of color how does one get students to move beyond their comfort zone and take action to meet individuals that are culturally different outside of the classroom? This paper describes the results of a textual analysis using grounded theory of student writing as they reflect on how to develop and implement effective communication strategies with individuals culturally and ethnically different from themselves outside of the classroom. The results of which might also be used to transform thinking about the diverse community surrounding the university and influence future decision-making on issues of social justice and human equality. © Common Ground, Annette Madlock.
Keywords: Grounded theory; Intercultural communication Competence; Multicultural classroom; Textual analysis; Undergraduates; dept.com; ⛔ No DOI found

Saladin and the truth of religion in Decameron I. 3 and X. 9 - Rhodes, J. (Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee, 2009)
Journal Abbreviation: Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee
Keywords: dept.eng

The use of controlled punishment and ritual in couples therapy - Lynch, B.J. (The Therapist's Notebook: Homework, Handouts, and Activities for Use in Psychotherapy, 2013)
Couples who come into therapy with amorphous symptoms often reveal later in treatment that there has been a traumatic event that occurred in the past and that has lingered as a significant disturbance to intimacy. No amount of “talk therapy? or insight seems to allow these couples to move past the point of emotional treachery. This activity is designed to allow these couples a vehicle for putting the past to rest in a way that allows them to continue their relationship without resentment, revenge, or continual pain. © 1998 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: The Therapist's Noteb.: Homework, Handouts, and Activities for Use in Psychotherapy
Keywords: dept.mft

Diagnosing race relations in management - Alderfer, Clayton P; Alderfer, Charleen; Tucker, L M; Tucker, Robert C (The Journal of Applied Behavioral Science, 1980)
This paper reports the theory, process, results, and consequences of diagnosing the race relations among managers of a large industrial corporation. A four person diagnostic team consisting of a black female, black male, white female, and white male, aided by a 12-person advisory committee of similar race/sex composition, developed an organic questionnaire and administered it to more than 600 managers. Data were collected and analyzed on general race relations, management groups, hiring, advancement, firing, actions for change, and reactions to the study. Analysis showed that the state of race relations in the company was related to a variety of systemic conditions including the ideas and feelings of individuals, the perceptions and actions of key groups, and the structure of the whole organization. As a result of the diagnosis, management committed itself to an action plan that addressed all the problematic issues uncovered by the diagnosis. © 1980, Sage Publications. All rights reserved.
82 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-316-845-829-383 tex.type: [object Object]
Keywords: dept.mft

Responses to carlotta regan tyler - Calvert, Linda Mcgee; Ramsey, V Jean; Alderfer, Charleen; Lynch, Barbara J (The Journal of Applied Behavioral Science, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-280-859-592-359 tex.type: [object Object]
Keywords: dept.mft

Catastrophic conditions in couple systems - Lynch, Barbara J (Journal of Couples Therapy, 1999)
A presentation of case studies forms the focus for an exploration of the discovery of an abortion or adoption used as the management of an unwelcome pregnancy which occurred in the context of the marital system. Managing an impasse in the middle phase of therapy in each case led to the emergence of information which then allowed the therapist to work with the couple system to alleviate the core situation out of which presenting problems emanated. In these cases the unwelcome pregnancy had the potential to be cataclysmic to the couple system. Therefore, the possibility that a couple is concealing an abortion or an adoption should be considered by couples' therapists when there is little or no response to usual strategies for change. The reason for concealment is immaterial. What is paramount is that the therapist bring the event to the fore of treatment and work with a couple to put closure on what is generally an unresolved issue. © 1999, by The Haworth Press, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-862-686-427-838 tex.type: [object Object]
Keywords: Abortion; Adoption; Grief; Pregnancy; dept.mft

Current status of family-based outcome and process research - Diamond, GS; Serrano, AC; Dickey, M; Sonis, WA (Journal of the American Academy of Child and Adolescent Psychiatry, 1996)
Objective: To review family-based treatment research. A growing body of research and several meta-analytic reviews demonstrate that family-based treatments are effective for a variety of child and adolescent disorders. In addition, an emerging tradition of family-based process research has begun to identify important ingredients of effective family psychotherapy. This article reviews these advances and their implications for future research. Method: Selected studies on the treatment of schizophrenia, depression, anxiety, eating disorders, attention deficit, conduct disorder, and substance abuse are reviewed, as well as several process research and meta-analytic studies. Results: Family-based therapies have been shown to be effective for treating schizophrenia, conduct disorder, and substance abuse. Some data support their effectiveness in the treatment of eating disorders. Few studies have targeted internalizing disorders. A process research tradition is emerging, but it is in need of methodological advances, Meta-analytic studies suggest that family-based therapies are as effective as other models. Conclusions: More well-designed studies with diverse populations are needed to assess accurately the effectiveness of this increasingly popular treatment approach.
57 citations (Crossref) [2023-10-31] tex.researcherid-numbers: diamond, Guy/X-8695-2019 tex.unique-id: ISI:A1996TL43200007
Keywords: anxiety; attention deficit disorder; child parent relation; depression; dept.mft; family therapy; feeding disorder; medical research; mental disease; outcome research; priority journal; process research; psychotherapy; review; risk factor; schizophrenia; substance abuse

Admissions criteria as predictors of performance in a family therapy doctoral program. - Piercy, Fred P; Dickey, Mitchell H; Case, Brian; Sprenkle, Douglas H; Beer, Jim; Nelson, Thorana S; Mccollum, Eric E (American Journal of Family Therapy, 1995)
This nine-year study examined the extent to which selected admissions criteria of 34 family therapy doctoral students predicted their future performance on clinical, academic, research, and other job-related criteria. Age and clinical background were positively related to clinical ratings after three years. Letters of recommendation and student autobiographies were positively related to qualify and quantity of publications. Graduate Record Examination scores and interview ratings were not predictive of any of the criterion variables at three or six years. Additional findings are presented and discussed.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-918-490-573-981 tex.type: [object Object]
Keywords: dept.mft

A structural family therapist responds to "A feminist critique of organizational humanism": - Lynch, Barbara J (The Journal of Applied Behavioral Science, 1994)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-326-030-576-507 tex.type: [object Object]
Keywords: dept.mft

The race relations competence workshop: theory and results - Alderfer, Clayton P; Alderfer, Charleen; Bell, Ella Louise; Jones, Jimmy (Human Relations, 1992)
This paper presents the theoretical basis and the associated perceptions of race relations that characterized a race relations competence workshop which served as the educational component of an overall program to improve race relations among managers within the fictitiously named XYZ Corporation. Workshop activities combined didactic and experiential methods and focused on group and individual levels of learning based on embedded intergroup relations theory. An assessment of the race relations competence workshop was carried out as part of an overall effort to evaluate the race relations improvement program in the company. Employing measures of both global evaluation and perceptions of race relations among managers, the study showed that Blacks evaluated the workshop more favorably than Whites, that reports of having information about the workshop were positively associated with favorable evaluations of the workshop, that workshop participants more than nonparticipants were likely to perceive Whites as hurting Blacks and less likely to perceive Blacks as hurting Whites. Additional analyses showed that, while the workshop generally had favorable effects for participants, the groups most likely to show unfavorable consequences were White male first level managers younger than 41 years and White female first level managers older than 40 years.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-048-778-075-671 tex.type: [object Object]
Keywords: dept.mft; race relations competence workshop

A biography of Edith Whitfield seashore - Alderfer, Charleen (The Journal of Applied Behavioral Science, 1992)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-878-753-412-999 tex.type: [object Object]
Keywords: dept.mft

An anatomy of bonding in the dyadic system - Lynch, Barbara J. (Journal of Couples Therapy, 1991)
Bonding is an essential factor in the establishment and maintenance of an intimate committed relationship. Dissecting elements of bonding leads to an understanding of the internal structure of the marriage. Attraction and bonding are different and equally vital in turning initial romance into enduring intimacy. The process of attraction based on projections developing into an enduring bond between peers merges relationship purpose and a rationale for emotional involvement. This occurs when attention is accorded to each of the factors of bonding; ego-equality, respect, interdependence and reality grounding. In therapy, a couple’s bonding can be assessed through the isomorphic qualities actualized in the therapeutic joining process. Discussions includes over bonded and under bonded couples, their presenting problems, and a treatment focus for each condition. © 1991 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00118 tex.type: [object Object]
Keywords: dept.mft

Fat in school: applied interdisciplinarity as a basis for consultation in oppressive social context - Clare, Mary M.; Ardron-Hudson, Elise A.; Grindell, Jessica (Journal of Educational and Psychological Consultation, 2015)
Children and youth in schools are subject to the effects of the larger culture's attitudes and values related to body size. When negatively biased, these attitudes and values can have detrimental effects and thus emerge as relevant to educational and psychological consultants. Drawing on the nascent field of Fat Studies with its focus on the cultural meanings attached to large bodies, we identify direct implications of fat phobia for school-age children and youth. Via a brief case example, an initial review of literature, and several examples of health-positive programming, we describe the social justice implications of fat phobia for consultants in school and community settings. In this consideration of the role of consultants for addressing fat bias and supporting health, we also suggest the merit of applied interdisciplinarity as a strong ground for consultation research and practice. The academic area of Fat Studies provides illustration of the integration of disciplinary perspectives (e.g., sociology, anthropology, biology, psychology). Educational and psychological consultation is ideally situated for systematically engaging such interdisciplinarity in support of practical outcomes that are healthy, sustainable, and socially just.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-800-206-439-585 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.mft

Theory into research practice: reflections and recommendations on collaborative feminist research - Harvey, Rebecca G.; Brown, Kristina S.; Miller, Bobbi J.; Williams-Reade, Jacqueline; Tyndall, Lisa; Murphy, Megan J. (Journal of Feminist Family Therapy, 2016)
Six women faculty came together to research their peers asking other women in COAMFTE-accredited programs about their personal and professional identities. The goal of this research was to develop recommendations for the field of Couple/Marriage and Family Therapy to support the engagement and advancement of women faculty. The research collaboration itself became a heuristic, feminist praxis, a co-creation of insight, support network, and professional relationships which had liberating results for the collaborators. We intended to create a research project that would be collaborative, empowering, and transformative for participants; in the process, the collaboration became empowering and transformative for ourselves. This article will reflect on our experiences and provide recommendations for future feminist research teams. Copyright © Taylor & Francis Group, LLC.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00155 tex.type: [object Object]
Keywords: clinical article; collaboration; dept.mft; family therapy; female; feminism; feminist research; gender; human; insider/outsider; marriage; university

Queer youth in family therapy - Harvey, Rebecca G.; Fish, Linda Stone (Family Process, 2015)
Trends in popular belief about same-sex relationships have undergone noteworthy change in the United States over the last decade. Yet this change has been marked by stark polarizations and has occurred at varying rates depending upon regional, community, racial, religious, and individual family context. For queer youth and their families, this cultural transformation has broadened opportunities and created a new set of risks and vulnerabilities. At the same time, youth's increasingly open and playful gender fluidity and sexual identity is complicated by unique intersections of class, race, religion, and immigration. Effective family therapy with queer youth requires practitioner's and treatment models that are sensitive to those who bear the burden of multiple oppressions and the hidden resilience embedded in their layered identities. We present case examples of our model of family therapy which addresses refuge, supports difficult dialogs, and nurtures queerness by looking for hidden resilience in the unique intersections of queer youths' lives. These intersections provide transformational potential for youth, their families and even for family therapists as we are all nurtured and challenged to think more complexly about intersectionality, sexuality, and gender. Las tendencias en la creencia popular acerca de las relaciones entre personas del mismo sexo han sufrido un cambio considerable en Estados Unidos durante la ultima decada. Sin embargo, este cambio se ha producido a ritmos diferentes segun las comunidades locales y regionales, y el contexto familiar individual. En el caso de los jovenes queer y sus familias, esta transformacion cultural ha ampliado oportunidades y creado un nuevo conjunto de riesgos y vulnerabilidades. Los jovenes queer y sus familias, al intentar desarrollarse en numerosos contextos, estan marcados por divergencias crueles en actitudes y creencias. Al mismo tiempo, la fluidez del genero y la identidad sexual cada vez mas abiertas y ludicas de los jovenes estan complicadas por intersecciones unicas de clase, raza, religion e inmigracion. Una terapia familiar eficaz con jovenes queer exige modelos de tratamiento y profesionales que sean sensibles a aquellas personas que cargan sobre sus espaldas numerosas opresiones y una resiliencia oculta incorporada en sus identidades multiples. Presentamos ejemplos de casos de nuestro modelo de terapia familiar que aborda el refugio, respalda los dialogos dificiles y apoya la sexualidad alternativa buscando la resiliencia oculta en las intersecciones unicas de las vidas de los jovenes queer. Estas intersecciones ofrecen posibilidades transformacionales para los jovenes, sus familias e incluso los terapeutas familiares mientras nos estimulan y nos desafian a todos a pensar de forma mas compleja acerca de la interseccionalidad, la sexualidad y el genero.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-905-145-849-804 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Family Relations; Family Therapy; Family therapy; Female; Gay; Gender Identity; Homosexuality; Homosexuality; Female; Homosexuality; Male; Humans; Interpersonal Relations; Lesbian; Male; Resilience; Social Identification; Social Isolation; Transgender Persons; Transgendered youth; United States; Vulnerable Populations; Young Adult; adolescent; dept.mft; family relation; family therapy; female; gender identity; homosexuality; human; human relation; lesbianism; male; male homosexuality; procedures; psychology; social behavior; social isolation; statistics and numerical data; transgender; vulnerable population; young adult

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-321-517-465-575 tex.type: [object Object]
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use

Sexual Identity Development and Heteronormativity - Harvey, Rebecca; Stone-Fish, Linda; Levatino, Paul (The Handbook of Systemic Family Therapy, 2020)
Sexual identity development has traditionally been theorized about from within heteronormative societies founded on patriarchal notions with links to misogyny, racism, and classism, among others. These forms of domination have constrained the way sexual identity has been conceived of, researched and written about within the mental health fields and limited the efficacy of clinical work with all people but especially sexual minorities and those who are gender non-binary. In this chapter the authors will deconstruct heteronormativity, examine the deleterious effect of it on mental health, and locate the influence of intersections of oppression on the field of SFT theory and in clinical work. An LGBTQI (lesbian, gay, bisexual, transgender, questioning, intersex) affirmative clinical framework developed from systems theory and queer theory will be outlined, and then a case study using the framework will be described.
Section: 22 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119788393.ch22
Keywords: LGBTQI; dept.mft; dept.swk; family therapy; heteronormativity; marriage and family therapy; sexual identity; systemic family therapy

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-482-460-077-460 tex.type: [object Object]
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-695-656-280-425 tex.type: [object Object]
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Lesbian couples - Stone Fish, Linda; Harvey, Rebecca (Encyclopedia of couple and family therapy, 2017)
Keywords: Current Political Climate; Difficult Dialogue; Donor Insemination; LGBTQ Community; Lesbian Couple; dept.mft